COMPLIANCE CONSUMPTION OF IRON TABLET SUPPLEMENT, CONSUMPTION OF ENHANCER AND INHIBITOR FOOD IRON SUBSTANCES BASED ON ANEMIA STATUS IN YOUNG WOMEN - Luh Putu Surya Eka Listiawati; Ni Made Dewantari; Ketut Lilik Arwati (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Anemia is a condition when hemoglobin in the blood is lower than normal. Based on the results of Riskesdas (2013), the prevalence of anemia in young women is still high. Efforts made to prevent anemia are by giving iron tablet supplements and regulating iron consumption and iron absorption inhibitors agents if consumed less than 2 hours before or after taking iron tablet supplements. The purpose of this study was to discuss the compliance of consume of iron tablet supplements, food enhancers and iron inhibitors and anemia status in young women. This research was observational and cross-sectional study with 57 samples conducted at SMP Negeri 2 Kerambitan in February until June. The collected data was processed based on each category and was presented in the form of distribution tables and cross tables, then analyzed descriptively. The results of this study found 18 samples (31.6%) had anemia and 27 samples who did not comply with iron tablet supplements. Of the 18 anemia samples, 12 samples did not comply with iron tablet supplements. Food iron enhancers that are often consumed are chicken meat while iron inhibitor foods that were often consumed are milk. Of the 18 samples there were anemia as many as 13 samples who often consumed chicken and 7 samples often consumed milk.